Coding 101 (Out of Print) - Davoren Chick (Association of American Medical Colleges, 2007)
Abstract Coding 101 is an online curriculum designed for residents. The curriculum includes three audiovisual modules and suggested supplementary online resources. While the audiovisual modules can be viewed in any order, they are designed for progressive learning in a suggested viewing order. Each module contains learning objectives for systems-based practice, an Accreditation Council for Graduate Medical Education general competency. Within each module, learning points are identified for PGY1-PGY3 progressive learning. For residents to best learn coding rules, the three modules should be viewed during PGY1, preferably during an ambulatory block experience when residents can focus on learning and applying coding principles. Residents should review the suggested resources after the related topics are introduced in the audiovisual modules. Clinic preceptors must also complete the modules, as many will need to learn the material as well. The first module, Coding Fundamentals, provides an overview of International Classification of Diseases, Current Procedural Terminology, Healthcare Common Procedure Coding System, and medical necessity rules. The second module, EM Coding, provides guided examples of outpatient evaluation and management coding using 1995 and 1997 rules. The third module, Beyond the Basics, introduces Modifier -25, Teaching Modifiers GE/GC, coding for counseling time, preventive care coding, and other miscellaneous topics. Supplementary suggested content allows learners to link to the Medicare 1995/1997 documents, the Centers for Medicare & Medicaid Services Evaluation and Management Services Guide, and other coding resources. The overall curriculum is appropriate for residents, fourth-year ambulatory students, fellows, and even faculty.